Information System Development With Comparison of Waterfall and Prototyping Models - yopi nugraha (Institut Pendidikan Indonesia, 2020)
The System Development Life Cycyle or better know as SDLC is the most commonly used method for developing information systems. SDLC consist of several stages, which include palanning, analysis, design, implementation, to maintenance. The concept in the SDLC underlies various types of software development to form a framework for planning and controlling the manufacture of information systems. SDLC models that are often used inlcude waterfall and prototyping. Thus, the comparison of the two models states that the waterfall model is more suitable for generic systems or software, meaning that the systems can identify all its needs form the start with general specification.